L’Atelier aurignacien découvert à Bușag (Nord-Ouest de la Roumanie). Données préliminaires. - Dobrescu, R.; Doboș, A.; Bobînă, A.; Bobînă, B. (Materiale și Cercetări Arheologice)
Rescue excavations carried out on the Bușag Hill in 2019 (the Palaeolithic site had been identified and excavated by Maria Bitiri in the 1960s and 1970s) allowed for new stratigraphic observations required by a future re-evaluation of the chronology. While we still await for the OSL results on the samples collected from trench II and the microscopic analysis of raw materials, the present paper presents preliminary observations on the lithic material from the Aurignacian workshop uncovered in soundings V and VI, level D : a homogenous assemblage ; two operational chains oriented towards blade production, predominant blade production ; possible presence of flake production ; predominant hard percussion, careful debitage, a certain massiveness of the lithic assemblage ; raw materials brought to the site in their natural form or with little modification